Analysis of Debt Effect on Profitability of Manufacturing Companies in Indonesia - Diana Fitria Ningsih; Doni Putra Utama (Pusat P2M Politeknik Negeri Batam, 2021)
This study aims to examine whether short term debt has a negative effect on company profitability and to test whether long term debt has a negative effect on the profitability of manufacturing companies in Indonesia which are listed on the Indonesia Stock Exchange during the 2014-2018 period. This study has 1 dependent variable namely profitability and uses 2 independent variables namely short term debt and long term debt, and uses 2 control variables namely liquidity and firm size. This study uses secondary data with database collection techniques. The sample of this study was 432 companies in 5 years of research. The data analysis technique used is multiple linear regression analysis through the application of SPSS 22. The results found that short term debt has a negative effect on company profitability and long term debt has a negative effect on company profitability. This shows that the lower the company's debt, the higher the profitability a company will get and otherwise.